EZH2 expression is restricted to malignant salivary gland tumors - Dusit BUMALEE; Prow JANJARUSSAKUL; Jintana PANKAM; Tawepong ARAYAPISIT; Nakarin KITKUMTHORN; Teerat CHANAMORN; Amanda Li Yin GOH; Puangwan LAPTHANASUPKUL (Journal of Applied Oral Science)
Abstract Background: Enhancer of zeste homolog 2 (EZH2) configures a histone methyl transferase enzyme that mediates the epigenetic silencing of target genes. Its overexpression has been related to tumor proliferation, metastasis, and poor prognoses. However, the study of this protein in salivary gland tumors (SGTs) remains limited. Objective: This study aimed to investigate EZH2 expression in common intra-oral SGTs, including pleomorphic adenoma (PA), mucoepidermoid carcinoma (MEC), and adenoid cystic carcinoma (ACC). Methodology: A total of 48 formalin-fixed paraffin-embedded tissue samples were analyzed, including 17 PA, 21 MEC, and 10 ACC cases. Immunohistochemical staining was performed using a rabbit recombinant monoclonal EZH2 antibody. EZH2 expression was described and quantified by the percentage of stained tumor cells. Results: Nuclear EZH2 expression occurred in most malignant SGTs (90.00% of ACC and 80.95% of MEC cases), whereas only one benign case of PA (5.88%) showed positive mild staining. Statistical analysis showed a significant difference in the mean of percentage positive cells in SGTs (p<0.001), particularly between benign and malignant SGTs (p<0.001). However, this study observed no significant differences between MEC and ACC (p=0.457). Conclusion: EZH2 expression significantly differed between malignant and benign SGTs, supporting its potential as a diagnostic marker for malignancy in these tumors.